Pengaruh Penggunaan Aplikasi SHUCADA (Smart Human Capital Database) Terhadap Kedisiplinan dan Kinerja Karyawan Studi pada PT. Studio Kami Mandiri - Satwika Mantara, I Gusti Ngurah Agung Indra; Suryani, Ni Kadek; Heptariza, Anita (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2025)
The utilization of digital technology in human resource management (HRM) plays a crucial role in enhancing employee discipline and performance. PT. Studio Kami Mandiri has implemented the SHUCADA application as an HRM system designed to improve work efficiency and employee discipline. This study aims to analyze the impact of the SHUCADA application on employee discipline and performance within the company. This research employs a quantitative approach using a pre-test post-test experimental method. Data were collected through questionnaires administered to 38 employees utilizing the SHUCADA application, along with log data from the application. Data analysis techniques included the Shapiro-Wilk normality test, validity and reliability tests, and hypothesis testing using paired t-tests and Pearson correlation to determine the relationships between the examined variables. The results indicate a significant difference in employee discipline and performance at PT. Studio Kami Mandiri before and after the implementation of the SHUCADA application (p=0.000). Furthermore, a strong positive correlation was found between the use of the SHUCADA application and increased discipline (r=1, p=0.000) as well as employee performance (r=1, p=0.000). These findings suggest that the SHUCADA application positively influences employee discipline and productivity.